Service life prediction of RC square piles based on time-varying probability analysis. (10th December 2019) - Xu, Qiuhong; Shi, Danda; Shao, Wei
Highlights: Monte-Carlo simulation method is applied in the service life prediction of RC square piles. The two-dimensional chloride diffusion model is used in RC square piles. The sensitivity of dominant factors for failure probability is analyzed. Dominant factors for the corrosion initiation period play an important role in the service life of RC square piles. Abstract: This paper proposes a time-varying probability analysis method for predicting the service life of reinforced concrete (RC) square piles. The theoretical model used for service life prediction is established under chloride ion ingression by determining the limit state equation of RC square piles. The Monte-Carlo simulation approach is applied to obtain the failure probability of RC square piles under different exposure time. The service life of RC square piles is obtained by determining the target failure probability. An example of the proposed approach is demonstrated to estimate the service life of RC square piles, and the analysis of the dominant factors is regulated to study the influence of random variables on the service life of RC square piles. The analysis results show that the dominant factors for corrosion initiation play an important role in the service life of RC square piles, and compared with the dominant factors during the crack initiation period, the service life of the RC square pile is more sensitive to changes of factors during the corrosion initiation period.